1998
DOI: 10.1021/cm970573j
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism, Phase Transformations, and Oxide Ion Conductivity in Bi1.56U0.22La0.22O3.33

Abstract: This paper deals with the polymorphism, phase transitions, and the oxide ion conduction of Bi1.56U0.22La0.22O3.33. Thermal treatment at 950 °C of a mixture of α-Bi2O3 and LaUO4+ x , followed by slow cooling to room-temperature, yields a hexagonal phase of that composition with cell parameters a H = 4.0066(7) and c H = 9.543(2) Å. Quenching of the reaction mixture from 950 °C leads to the formation of a cubic fluorite-type phase with a c = 5.6273(8) Å. Annealing of both cubic and hexagonal phases at 600 °C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…8 A simple operation transforms a f.c.c.-type cell into a hexagonal cell: We have previously studied the electrical properties of trigonal Bi 2.34 U 0.33 La 0.33 O 5 . 7 The conductivity at 300 ЊC (σ 300 ЊC = 2.5 10 Ϫ5 S cm Ϫ1 ) shows that this material is a good solid ionic conductor. The conductivity is assigned to the O 2Ϫ motion through the anion vacancies in the oxygen network.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…8 A simple operation transforms a f.c.c.-type cell into a hexagonal cell: We have previously studied the electrical properties of trigonal Bi 2.34 U 0.33 La 0.33 O 5 . 7 The conductivity at 300 ЊC (σ 300 ЊC = 2.5 10 Ϫ5 S cm Ϫ1 ) shows that this material is a good solid ionic conductor. The conductivity is assigned to the O 2Ϫ motion through the anion vacancies in the oxygen network.…”
Section: Discussionmentioning
confidence: 94%
“…8 The oxide-ion conductivity shown by the several Bi 1.56 -U 0.22 La 0.22 O 3.33 polymorphs is rather different. 7 At 300 ЊC the monoclinic phase shows the lowest conductivity, σ = 6.6 × 10 Ϫ7 S cm Ϫ1 . For the trigonal polymorph a remarkable increase of conductivity by two orders of magnitude is observed, σ = 2.5 × 10 Ϫ5 S cm Ϫ1 .…”
mentioning
confidence: 99%
“…Thus, in similar Bibased oxides it has been reported that the corresponding cubic phase is transformed into a phase of lower symmetry Table 1 Activation energy (E) and pre-exponential factor (r 0 ) obtained from the fitting of the two straight lines of Fig. 5 Temperature range (-C) E (eV) r 0 (S cm À 1 ) 120 -500 0.96 T 0.01 (1.2 T 0.1) Â 10 5 600 -900 0.42 T 0.02 60 T 10 (hexagonal or monoclinic phase) after heating for a long period at 600 -C (aging) [29,30].…”
Section: Thermal Stability and Agingmentioning
confidence: 99%
“…Polymorphic phases of a material give an excellent opportunity to study the inter-relations of physical properties with different arrangements of the same set of atoms. The interatomic distances between the atoms, that is, the types of atomic bonds or the types of orbital overlapping, play a key role in controlling the physical parameters. A material, subjected to a particular environment or condition, prefers to form in a crystal structure having minimum formation energy.…”
Section: Introductionmentioning
confidence: 99%